What does Milton’s God Want?—Human Nature, Radical Conscience, and the Sovereign Power of the Nation-State - Gil, Daniel Juan (Literature and theology, 2014)
This article responds to William Schweiker's challenge (issued in, among other places, an article published in Literature and Theology) to find a way of saving moral realism—rooted in the value of fulfilling and developing human capabilities—from the danger of taking human capabilities as the only good, thus leading to unchecked humans way over the world. I argue that the political theology perspective of Carl Schmitt and Giorgio Agamben provides a basis for an ethics that is at once rooted in human capabilities and yet does not take human capabilities as its sole standard of value. The capabilities approach to ethics presumes an account of human nature as universal and transhistorical. I argue, by contrast, that any particular account of what human nature is (and therefore what human capabilities are) is the product of a historically contingent political community. Moreover, I argue that a political order can define and enforce a distinctive vision of human nature (and human capabilities) only by appeal to something outside of itself, a transcendental warrant. Such a transcendental warrant shadows even avowedly secular political orders; when it is made the object of theological reflection it turns out to provide a positive ethical principle that checks and corrects any ethics based on developing human capabilities. I argue that the great Protestant writer John Milton combines political theory and early modern theology in a way that brings to light the ethical potential of the transcendental warrant built into any actually existing political community. In The Tenure of Kings and Magistrates, Paradise Lost and his writings on marriage, Milton argues that concrete ethical norms are always tied to a particular account of human nature that is the contingent achievement of political power. The function of Milton's God is to countersign a historically contingent structure of political power and the version of human nature it enshrines. But because Milton’s God is ultimately outside all politically mediated definitions of human nature, Milton’s God also stands for loosening and disrupting any particular understanding of human capabilities.